SOLIDWORKS-COSMOSWORKS PACKAGE ADAPTATION FOR THE SOLUTION OF PROBLEMS OF MODELLING OF COOLED SHOVELS OF GAS TURBINES THERMOINTENSE CONDITIONS - Карпінос, Б.; Куліш, В. (Science-based technologies, 2012)
For integral plate and plate with a hole analytical and numerical results for two test problems thermal and thermotension slate are given . Results of calculation have shown, that SolidWorks-COSMOSWorks package can be effectively used for solution of material states modeling tasks of cooled gas turbine blade.